Penyuluhan Peningkatan Pendapatan dan Pengembangan Pasar Wisata Ladang Edukasi - Murad Daulay, M. Safii; Hasanah, Uswatun; Prayogi, Oki; Fatmasari, Ayunda (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity aims to assist the managers of Wisata Ladang Edukasi in increasing income and expanding market reach. A team of lecturers from Universitas Tjut Nyak Dhien, supported by Management students, provided guidance as a form of academic contribution to society. Wisata Ladang Edukasi combines elements of education and recreation but still faces challenges in marketing strategies and business management. The method used was counseling through direct dialogue, delivery of marketing materials, and interactive discussions. The results showed that the managers gained new insights on market segmentation, the importance of digital promotion, and improving services based on visitor needs. The activity also raised community awareness of the potential of educational tourism as a sustainable income source. For students, this was a valuable opportunity to apply management theories in real situations and develop soft skills such as communication and teamwork. Overall, the activity contributed to enhancing the partners' capacity and strengthening the university's role in community development.